Peran Guru Tahfiz dalam Meningkatkan Motivasi Siswa untuk Menghafal Al–Quran di Rumah Tahfiz Asshadiq Aur Birugo Tigo Baleh - Fajri, Ahmad; Husni, Arman (Lembaga Yasin AlSys, 2023)
Students are still not perfect in pronouncing the tajwid letters and it is difficult to memorize the Al-Qur'an because students are still playing around a lot and are not serious in memorizing the Al-Qur'an. Therefore, the role of the tahfiz teacher is needed to motivate students to memorize the Qur'an at the ASSHADIQ Aur Birugo Tigo Baleh tahfiz house. This type of research is field research (fried research) which is descriptive qualitative in nature. The key informant in this study was the ASSHADIQ tahfiz teacher Aur Birugo Tigo Baleh while the supporting informants were ASSHADIQ Aur Birugo Tigo Baleh students. Researchers used observation techniques, interviews and supported by documentation. The collected data is then analyzed using data analysis techniques. From the research conducted by the author, it can be concluded that the role of the tahfiz teacher in increasing students' motivation in memorizing the Qur'an is: the tahfiz teacher's responsibility for discipline is to invite, guide, and motivate students to memorize the Al-Qur'an at tahfiz's home ASSHADIQ Aur Birugo Tigo Baleh. The teacher informs the fast time in memorizing the Al-Qur'an, namely during the last third of the night, after performing the dawn and midday prayers, this time makes it easier to memorize the Al-Qur'an. The knowledge that the teacher gives to students is the virtue of someone who memorizes the Al-Qur'an and there are many virtues such as: being able to intercede for the family, getting a noble position before Allah SWT. The teacher guides students who have problems memorizing the Qur'an by coming to them, communicating directly with students and asking what problems they are facing. The teacher provides training to students by memorizing the Al-Qur'an to educate the brain and form good and polite character.